2014
DOI: 10.1017/ice.2014.39
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities, Exposure to Medications, and the Risk of Community-Acquired Clostridium difficile Infection: A Systematic Review and Meta-analysis

Abstract: background. Clostridium difficile infection (CDI) has been extensively described in healthcare settings; however, risk factors associated with community-acquired (CA) CDI remain uncertain. This study aimed to synthesize the current evidence for an association between commonly prescribed medications and comorbidities with CA-CDI. methods. A systematic search was conducted in 5 electronic databases for epidemiologic studies that examined the association between the presence of comorbidities and exposure to medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
108
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 47 publications
9
108
1
5
Order By: Relevance
“…While antibiotic exposure is a key risk factor for CDI [1,[31][32][33], our study has again demonstrated that over a third of CA-CDI cases were associated with no recent history of a prescribed antibiotic, as seen in other studies [22,[34][35][36][37]. Indeed, we found that CA-CDI cases were nearly twice as likely to have had no antibiotics preceding infection than HA-CDI cases (p < 0.0001).…”
Section: Discussionsupporting
confidence: 82%
“…While antibiotic exposure is a key risk factor for CDI [1,[31][32][33], our study has again demonstrated that over a third of CA-CDI cases were associated with no recent history of a prescribed antibiotic, as seen in other studies [22,[34][35][36][37]. Indeed, we found that CA-CDI cases were nearly twice as likely to have had no antibiotics preceding infection than HA-CDI cases (p < 0.0001).…”
Section: Discussionsupporting
confidence: 82%
“…Although exposure to antibiotics remains the most documented risk factor for CDI, attention has recently been directed toward a plausible link with PPIs. Several systematic reviews and meta-analyses have shown that PPIs are significantly associated with increased risk of primary or recurrent CDI [18,19,20]. In 2012, Janarthanan et al [19] reviewed 17 case-control studies and 6 cohort studies from 1990 to 2010 to evaluate the association between PPIs and CD-associated diarrhea (CDAD), and demonstrated that the overall risk estimate (OR) was 2.31 (95% CI 1.72-3.10) and 1.48 (95% CI 1.25-1.75) for cohort and case-control studies respectively (Table 1).…”
Section: Infectious and Inflammatory Diseases Possibly Associated Witmentioning
confidence: 99%
“…Common risk factors for community or hospital acquired C. difficile infection (CDI) are comorbid diseases and exposure to any class of antibiotics. 1,2 Comorbid inflammatory bowel disease (IBD) is considered the most significant risk factor for the acquisition of CDI in the community setting. 1 Previous research has shown that the likelihood of infection is increased by many factors including, but not limited to, healthcare system contact, nutritional deficiencies, and antibiotic exposure.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Comorbid inflammatory bowel disease (IBD) is considered the most significant risk factor for the acquisition of CDI in the community setting. 1 Previous research has shown that the likelihood of infection is increased by many factors including, but not limited to, healthcare system contact, nutritional deficiencies, and antibiotic exposure. 25 CDI is an increasingly prevalent infectious complication in the IBD patient population.…”
Section: Introductionmentioning
confidence: 99%